Las emociones como variables relacionadas con el cambio de hábitos de salud en familiares y amigos próximos de enfermos de cáncer - Soto, Josefa; Planes, Montserrat; Gras, Maria Eugènia (Psicooncología, 2003)
Study of the changes in health habits of 105 cancer patients’ relatives and close friends after the diagnosis. The aim is to try to verify whether the knowledge of the disease has got some impact in the modification of their life styles. The emotional alterations influence in this change of behaviour has been analysed futhermore. An interview of own creation and HADS (Anxiety Hospital and Depression Scale of Zigmond and Snaith, 1983) instrument, in a Spanish and a Catalan version, were used with this aim. The results show that 21.1% of the participants presented positive changes in their health habits after the diagnosis of the relative or close friend and 11.5% showed negative changes. In relation to the role of the emotions, averages of anxiety (14,33; d.t.=4,98) and depressive (10,17; d.t.=4,93) symptoms were higher in those subjects who made negative changes than in those who did not make any change (9,32; d.t.=5,37 and 6,33; d.t.=4,64). In addition, the youngest participants, with more depressive symptoms and who visit the subject more often, are those who become more assets modifying health habits. The results suggest that emotional alterations, mainly depressive symptoms, are associated with negative change and, therefore, it would be suitable to lend some type of attention to these alterations in the population studied with the purpose of improving their present and future health.